Robust Hydrophobic Rare Earth Oxide Composite Electrodeposits. Issue 24 (7th November 2017) - Tam, Jason; Palumbo, Gino; Erb, Uwe; Azimi, Gisele
Abstract: Inspired by the lotus leaf, nonwetting surfaces have drawn widespread attention in the field of surface engineering due to their remarkable water repelling characteristics. There are many applications for these surfaces, for instance, self‐cleaning walls and windows, anti‐icing surfaces, or low drag microfluidic channels. However, the adoption of nonwetting surfaces in large scale industrial applications has been hampered by synthesis techniques that are not easily scalable and the limited long term stability and wear robustness of these surfaces in service. This study demonstrates a simple, low cost, and scalable electrochemical technique to produce robust composite coatings with tunable nonwetting properties. The composite coatings are composed of an ultrafine grain nickel matrix with embedded hydrophobic cerium oxide ceramic particles. A comprehensive characterization is performed, including wetting property measurements, electron microscopy, focused ion beam analysis, hardness measurements, and abrasive wear testing to establish the structure–property relationships for these materials. The ultrafine grain structure of the nickel matrix contributes to the high hardness of the composites. As a result of the bimodal CeO2 particle size, hierarchical roughness is present on the surface of the composite, leading to remarkable nonwetting properties, even after 720 m of abrasive wear. Abstract : Here a simple and scalable electrochemical technique is demonstrated to produce robust composite coatings with tunable hydrophobicity. The coatings are composed of an ultra‐fine grain Ni matrix with embedded hydrophobic CeO2 particles. It is demonstrated that these composite materials sustain their hydrophobicity even after prolonged abrasive wear; hence, it is expected that they find widespread applicability as robust hydrophobic materials.